Minds and bodies : an introduction with readings - Wilkinson, Robert, 1948- (Routledge, 2000)
This work is an introduction to the mind-body problem. Written with the beginner in mind, Robert Wilkinson carefully introduces the reader to the fundamental components of the philosophy of mind.